Update on Perineuronal Net Staining With Wisteria floribunda Agglutinin (WFA) - Härtig, Wolfgang; Meinicke, Anton; Michalski, Dominik; Schob, Stefan; Jäger, Carsten (Frontiers in Integrative Neuroscience, 2022)
As chemically specialized forms of the extracellular matrix in the central nervous system, polyanionic perineuronal nets (PNs) contain diverse constituents including chondroitin sulfate proteoglycans (CSPGs), hyaluronic acid and tenascins. They are detectable by various histological approaches such as colloidal iron binding and immunohistochemical staining to reveal for instance the CSPGs aggrecan, neurocan, phosphacan and versican. Moreover, biotin-, peroxidase- or fluorescein conjugates of the lectins Vicia villosa agglutinin and soybean agglutinin enable the visualization of PNs. Currently, the N-acetylgalactosamine-binding Wisteria floribunda agglutinin (WFA) is the most widely applied marker for PNs. Therefore, this article is largely focused on methodological aspects of WFA-staining. Notably, fluorescent WFA-labelling allows after its conversion in electron-dense adducts also electron microscopic analyses. Furthermore, the usefulness of WFA-conjugates for the oftentimes neglected, in vivo and in vitro labeling of PNs is emphasized. Subsequently, we discuss impaired WFA-staining sites after long-lasting experiments in vitro and especially in autoptic brain samples with long post mortem delay and partial enzymatic degradation - while immunolabeling of aggrecan and CSPG link proteins under such conditions has proven more robust. In some hippocampal regions from perfusion-fixed mice, more PNs are aggrecan-immunoreactive than WFA-positive, whereas the retrosplenial cortex displays many WFA-binding PNs devoid of visible aggrecan-immunoreactivity. Additional multiple fluorescence labeling exemplarily revealed in ischemic tissue diminished staining of WFA-binding sites and aquaporin 4 and concomitantly upregulated immunolabeling of neurofilament, light chains and collagen IV. Finally, we briefly discuss possible future staining approaches also based on nanobodies to facilitate novel technologies revealing details of net morphology.